SIFAT FISIK DAN ORGANOLEPTIK BAKSO YANG DIBUAT DARI DAGING SAPI DENGAN LAMA PELAYUAN BERBEDA - Nordiansyah Firahmi; Siti Dharmawati; Mofie Aldrin (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
The study aims to determine physical and organoleptic properties of meatballs made of beef with old withering different. The research was conducted by the using a completely randomized design (CRD) comprised of 5 treatments and 5 replicates ie: P0 = Without treatment (control), P1 = Withering beef for 5 days, P2 = Withering beef for 6 days, P3 = Withering beef for 7 days P4 = Withering beef for 8 days. Experimental design to test the physical properties such as pH and beef meatballs folding test, the data were analyzed of variance (ANOVA), if there is significanlty continued with Duncan test. Data obtained on organoleptic test in the form of aroma, flavour, color and texture of beef meatballs were analyzed with nonparametric tests (Kruskal Wallis). The results showed that the taste meatball most preferred panelists to treatment with the use of meat withered for 7 days (P3) of 5:23 (rather savory) that tastes almost the same with meatballs that use fresh meat without withering (P0) at 5:20 rather savory). All treatments withering flesh produces a rather bright color. Meatball most preferred color panelists to treatment with the use of meat withering for 8 days at 4.99. Texture of the best meatballs in treatment using fresh meat without withering of 5:29 (a bit chewy).Key word: withering, beef meat, meatballs, physical, organoleptic